The Impact of Oil Prices on the Macroeconomic Indicators of Kazakhstan and the Consequences for the Formation of Social Policy - Moldabekova, Gulmira; Raimbekov, Zhanarys; Tleppayev, Arsen; Tyurina, Yuliya; Yesbergen, Raushan; Amaniyazova, Gulimai (International Journal of Energy Economics and Policy, 2022)
The article analyzes the impact of the dynamics of oil prices on the main macroeconomic indicators of the Kazakhstani economy and the consequences of the formation of national social policy. The article applies different hypotheses about the sensitivity of macroeconomic indicators of the economy of Kazakhstan to fluctuations of oil prices, and in addition, it specifies and evaluates a system of simultaneous equations that allows to test these hypotheses. Scenarios for the reaction of the Kazakhstani economy to exogenous shocks associated with a sharp change in the level of oil prices are considered, and some measures are proposed to reduce the negative consequences of fluctuations in oil prices for the Kazakhstani economy. Finally, the article discusses some of the results of understanding the challenges and realities in the field of social policy, which are generated by the model of economic growth.